Photon Recycling Effect and Lossless Fluorescence Propagation in β‐Sheet Peptide Fibers. Issue 4 (22nd December 2021) - Apter, Boris; Lapsker, Igor; Inberg, Alexandra; Rosenman, Gil
Abstract: Light‐delivering optical fibers are widely used for biomedical imaging, theranostics and surgery, and optogenetics. In this work, a new generation of bioinspired optical fibers is proposed. Developed amyloidogenic peptide fibrillary structures with tailored β‐sheet conformation exhibit unique optical properties of full overlapping of broadband visible fluorescence (FL) and optical absorption spectra. This study reports on unexpected lossless propagation of the FL light along 100 µm length β‐sheet microfibers. It is shown that the found FL long‐distance lossless radiative energy transport occurs due to highly effective FL photon recycling phenomenon supported by FL zero Stokes shift and high quantum yield. This new non‐Beer–Lambert FL lossless propagation mechanism is observed in very thin ≈1 µm diameter fibers, providing a single/few‐mode waveguiding regime. The developed model and computer simulations, based on the finite difference time domain method, are consistent with the experimental results. Fabricated peptide FL fiber probes permit delivering intensity‐modulated FL signal with selected wavelength over the whole visible spectrum in wide modulation frequencies range. Abstract : Amyloidogenic peptide fibrillary structures with tailored β‐sheet conformation exhibit unique optical properties of total overlapping of broadband visible fluorescence and optical absorption spectra. Unexpected lossless fluorescent light propagation along 100 µm length β‐sheet microfibers occurs due to the highly effective photon recycling phenomenon. This new lossless propagation mechanism is observed in thin fibers, providing a single/few‐mode waveguiding regime.